THE BLENDED LEARNING IMPLEMENTATION OF ELT BASED ON TEACHERS AND STUDENTS’ PERSPECTIVE IN NEW NORMAL CONDITION OF COVID 19 - Lukman Arif Rachman; Sudiyono Sudiyono; Elzi Phonix (PROJECT (Professional Journal of English Education), 2021)
This study aims to determine the perceptions of teachers and students towards the implementation of blended learning in English, at high schools in the city of Bandung. The research method adopted for this research is the mix method between qualitative and quantitative. Participants  involved were teachers and students taken randomly from as many as nine senior high schools spread across the city of  Bandung. The technique and data processing were carried out by distributing a questionnaire that each participant had to fill in, the questionnaire   contained seven aspects of how they responded to the advantages each of both teachers and students due to the English blended learning method. After the data were collected, then an analysis was carried out by calculating on the perceptions of teachers and students. The main advantage according to the teachers perception was challenging for teachers in preparing the material and using the media (93% perception responses). Meanwhile, the main advantage according to students perception was that English blended learning could improve their language skills (77% perception responses). As suggestions, it can be conveyed that blended learning can be continued for this era of Covid 19. Keywords:  English, Blended Learning, Teachers’ Perspective, Students’ Perspective